Analysis of diffraction spectra of periodic gratings, the profile of which is described by electrocardiograms - Migel, Anton S.; Maly, Sergei V. (Journal of the Belarusian State University. Physics, 2025)
The use of a model problem on the interaction of a plane linearly polarised electromagnetic wave with the interface of two media, the profile of which is described by a periodic signal, for the formation of a feature vector (diffraction descriptor) in the form of amplitudes of propagating spatial harmonics of a scattered field is considered. The object of the study is electrocardiogram signals. Algorithms for preprocessing electrocardiogram signals to isolate normalised cardiocycles used to form periodic grating models with specified vertical and horizontal scaling coefficients with respect to wavelength are proposed. The results of calculations of diffraction descriptors for three types of electrocardiograms corresponding to different states of the cardiovascular system, obtained under different modes of scaling, fixed angle of incidence and polarisation of the electromagnetic wave, are presented. It has been established that diffraction descriptors are highly sensitive to the peculiarities of electrocardiogram signals and, with the same scaling coefficients of cardiocycles, can be used in the construction of automated diagnostic systems.